2018
DOI: 10.1111/apt.15013
|View full text |Cite
|
Sign up to set email alerts
|

Persistent damage on magnetic resonance enterography in patients with Crohn’s disease in endoscopic remission

Abstract: Summary Background In Crohn's disease, it is essential to distinguish between persistent damage and abnormalities that can heal with anti‐inflammatory therapy. Aim To assess magnetic resonance enterography (MRE) lesions that persist in patients in long‐standing endoscopic remission, analyse their relationship with baseline characteristics, and determine their prognostic implications. Methods We systematically reviewed pre‐ and post‐treatment MRE findings in patients with Crohn's disease and severe inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 25 publications
(64 reference statements)
3
27
0
1
Order By: Relevance
“…Patients receiving escalated dosages of anti-TNFs or for the indication of postoperative recurrence in Crohn’s disease had a >75% risk of relapse on drug withdrawal. Persistent abnormalities on MRE in Crohn’s disease patients in endoscopic remission also makes relapse more likely 851. Decisions regarding withdrawal should be taken in the context of the individual patient, their disease history and the consequences of relapse 852…”
Section: Common Disease Considerationsmentioning
confidence: 99%
“…Patients receiving escalated dosages of anti-TNFs or for the indication of postoperative recurrence in Crohn’s disease had a >75% risk of relapse on drug withdrawal. Persistent abnormalities on MRE in Crohn’s disease patients in endoscopic remission also makes relapse more likely 851. Decisions regarding withdrawal should be taken in the context of the individual patient, their disease history and the consequences of relapse 852…”
Section: Common Disease Considerationsmentioning
confidence: 99%
“…Altered MAT near the affected intestinal area is considered to be characteristic of severe CD [6,[27][28][29][30]. Persistent alterations in this tissue even after endoscopic remission can be observed by magnetic resonance imaging [31], and may be associated with a complicated disease course and abdominal surgery in CD [32]. There is now more evidence to link intestinal and mesenteric abnormalities in CD, and this knowledge may influence clinical and surgical management of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Complete response to therapy as shown by resolution of all imaging findings of inflammation at US, CT and MR enterography is termed "transmural healing", as these cross-sectional techniques image the bowel wall. Of note, abnormalities on crosssectional imaging, such as wall thickening, strictures and creeping fat, frequently persist, despite achieving endoscopic remission [32]. MR enterography has an approximately 90% accuracy for mucosal healing [33], and other studies have demonstrated improved outcomes or prediction of clinical remission with transmural healing [34,35].…”
Section: Treatment Strategy and Evolving Role Of Imagingmentioning
confidence: 99%